2021
DOI: 10.3389/fimmu.2021.757669
|View full text |Cite
|
Sign up to set email alerts
|

A Chaperone-Like Role for EBI3 in Collaboration With Calnexin Under Inflammatory Conditions

Abstract: The interleukin-6 (IL-6)/IL-12 family of cytokines plays critical roles in the induction and regulation of innate and adaptive immune responses. Among the various cytokines, only this family has the unique characteristic of being composed of two distinct subunits, α- and β-subunits, which form a heterodimer with subunits that occur in other cytokines as well. Recently, we found a novel intracellular role for one of the α-subunits, Epstein-Barr virus-induced gene 3 (EBI3), in promoting the proper folding of tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…Since EBI3 has multiple functions in immune regulation, we might need to consider other functions of EBI3. EBI3 binds to IL-12p35 and IL-23p19 and functions as heterodimer cytokines named IL-35 and IL-39, respectively (5). EBI3 also serves as a molecular chaperone in conjunction with calnexin in CD4 + T cells during inflammation (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since EBI3 has multiple functions in immune regulation, we might need to consider other functions of EBI3. EBI3 binds to IL-12p35 and IL-23p19 and functions as heterodimer cytokines named IL-35 and IL-39, respectively (5). EBI3 also serves as a molecular chaperone in conjunction with calnexin in CD4 + T cells during inflammation (45).…”
Section: Discussionmentioning
confidence: 99%
“…EBI3 is expressed in a variety of immune cells (1)(2)(3), and its expression is induced by stimulation of Toll-like receptors (TLRs) (4). It binds to IL-27p28 and functions as a heterodimer cytokine named IL-27 (5). IL-27 is a cytokine that functions in both innate and acquired immunity.…”
Section: Introductionmentioning
confidence: 99%
“…CANX (calnexin), an endoplasmic reticulum (ER) lectin chaperone, participates in the synthesis of HLA class I surface antigen complex, protein folding, cellular energy balance, and autophagy-related process in several ways [24][25][26][27]. Azuma Y et al found that CANX and CRT could be translocated to the cell surface by cellular stresses and chemotherapeutic drugs, such as mitoxantrone.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the human IL-27p28 has only one cysteine residue and therefore lacks a disulfide-bond, instead requiring EBI3 binding for its secretion ( 10 , 13 , 43 46 ). The EBI3 subunit acts as chaperone-like protein and this property facilitates the secretion of non-disulfide-linked IL-27, IL-35, and IL-39 ( 45 , 47 ).…”
Section: Il-27/il-27r Signalingmentioning
confidence: 99%
“…EBI3 is induced under inflammatory conditions and independently secreted, even in the absence of the subunits IL-27p28, IL-35p35 or IL-39p19. This has led to the hypothesis that EBI3 plays additional roles including a chaperone-like and regulatory functions ( 47 , 67 , 70 , 71 , 81 , 82 ).…”
Section: Il-27 Expression In Lymphoid and Peripheral Tissuesmentioning
confidence: 99%